The economic consequences of discrete recognition and continuous measurement - Gao, Pingyang; Jiang, Xu (Journal of Accounting and Economics, 2020)
Discrete recognition is a long-standing and ubiquitous accounting practice, but it has been widely criticized for suppressing information and inducing accounting-motivated transactions. We study a model to examine the economic consequences of shifting away from discrete recognition to a continuous measurement approach. Without manipulation, discrete recognition is less informative than the continuous approach. However, the continuous regime induces more manipulation. The equilibrium informativeness is determined by both the accounting standard and endogenous manipulation. Discrete recognition is more informative than its continuous counterpart precisely when manipulation is a severe threat. We respond to the recent call in Kothari, Ramanna, and Skinner (2010) for using positive accounting theory to explain certain long-standing accounting practices. We also discuss the model's implications for fair value accounting.